A bizalom hatása a munkaerő-piaci helyzetre = Trust and its effects ont he labour market - Lazányi, Kornélia (Közép-Európai Közlemények, 2018)
Trust is an interpersonal phenomenon, which is hard to capture since it has various definitions across disciplines. In present paper trust is analysed as a social phenomenon that determines the functioning of societies and the embedded organisations. After a short review of international research data and the relevant results of the European Social Survey (2017) the preliminary data of a research financed through the New National Excellency Program are presented. According to the findings of the research, the members of the Z generation are even less trusting than their older peers are; which is an important fact, since they have other motivators than the members of X and Y generation had. As the results indicate, organisations and mainly superiors need to adapt to the expectations of the new generation on the labour market. Trust is a central notion of this change. Leaders should transform their style to meet the requirements of a trusting organisational culture. By doing so, they will not only reap the benefits of interpersonal trust, such as creativity, innovativeness, increased efficiency and commitment, but can create a comparative advantage for their companies on the labour market.